Chiral 5-phenylpyrimidine liquid crystals with 'de Vries-like' properties: dependence of electroclinic effect and ferroelectric properties on carbosilane nanosegregation. Issue 36 (26th August 2016) - Schubert, Christopher P. J.; Müller, Carsten; Giesselmann, Frank; Lemieux, Robert P.
Abstract : The effect of nanosegregation on electroclinic effect and ferroelectric properties in carbosilane-terminated 'de Vries-like' mesogens. Abstract : A homologous series of tri-, di- and monocarbosilane mesogens with a 5-phenylpyrimidine core and a chiral ( S, S )-2, 3-difluorohexyloxy chain were synthesized and characterized. We show that shortening the carbosilane end-group has a detrimental effect on 'de Vries-like' properties, causing an increase in reduction factor R from 0.17 for the tricarbosilaneQL32-6 to 0.38 for the monocarbosilaneQL34-6, both at the point of maximum layer contraction upon transition from the orthogonal SmA* to the tilted SmC* phase. This increase in R correlates with an increase in birefringence Δ n, a broadening in the SmA* temperature range and a decrease in optical tilt angle θ opt in the SmC* phase, which are all consistent with an increase in orientational order and a decrease in lamellar order. The electroclinic effect (ECE) in the SmA* phase decreases with decreasing length of the carbosilane end-group, which is consistent with previous observations of high ECE in 'de Vries-like' liquid crystals. On the other hand, spontaneous polarization P S measurements suggest that polar ordering in the SmC* phase is not strongly dependent on R .